Commitment-based Management in the Spare Parts Warehouse Area of a Car Dealership in Lima - Segovia Olazábal, Cristian Maurizio (2022)
The automotive sector is a large player in the Peruvian economy; however, it has been affected in recent years by the political situation, changes in the tax code and high competitiveness in the sector, which has mainly affected commercial results. In this situation, the need to develop a management tool that helps lead teams in this sector and that is applied to the Peruvian reality becomes important. This study focused on the spare parts warehouse team belonging to the after-sales management of a car dealership in Lima. Likewise, the study shows the implementation of Commitment-based Management as a management and direction tool to improve the gross margin obtained by the sub-management in charge, by verifying its effectiveness in the results of the period analyzed.